Aplicación de un Modelo de Preservación Digital para Garantizar la Integridad al Largo Plazo de la Información de Archivos del GADM-Riobamba - Ausay Espinoza, Mayra Fernanda (2019)
The non-existence of a computer system with a confidential model of digital preservation, which helps to make the process of preservation of the historical files of the GADM - RIOBAMBA which has been affected in the process of searching information The present project is based on the application of the model PREDECI of digital preservation, by means of development of a software which will allow to manage processes focused on the papers of the Department of Documentary Management of the Municipality of Riobamba. For that reason , it was analyzed the model PREDECI , this model was applied and the usefulness was evaluated by guaranteeing the integrity of the information of the Department through skills of preservation., aligned to the targets of the GADM-Riobamba, being a flexible model which could be adapted itself to the changes in the institutional processes, Furthermore the model is independent from the technology of development of software. For the development of the Computer System with the model, the specification of requirements of software is based on the functional entities which is devided into a set of three levels and eight entities, those entities preserve and specify how to manage and transmit the information, helping to preserve the production of files, adding a control of acces